2014
DOI: 10.1097/wnr.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate into the insular cortex during conditioned taste-aversion acquisition delays aversive taste memory extinction

Abstract: Histone acetylation is one mechanism that promotes gene expression, and it increases during learning of various tasks. Specifically, novel taste consumption produces an increased acetylation of histone lysine residues in the insular cortex (IC), where protein synthesis is crucial during memory consolidation of conditioned taste aversion (CTA). However, the role of this elevated histone acetylation during CTA learning has not been examined directly. Thus, the present study investigated the effects of sodium but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Subsequent studies have expanded on the role of epigenetic mechanisms in the IC – in particular, histone acetylation – to regulate aversive memory for conditioned taste. A 2014 study by Nuñez-Jaramillo and colleagues ( Núñez-Jaramillo et al, 2014 ) found that infusing the general class I HDAC inhibitor, sodium butyrate (NaB), in the IC during CTA strengthened the associative memory between the taste cue and malaise, which was revealed behaviorally as delayed extinction of the taste aversion. The same effect of HDAC inhibition on CTA memory was also reported by ( Rodríguez-Blanco et al, 2019 ) with post-training IC injections of the HDAC1/3-selective inhibitor MS-275 (“entinostat”).…”
Section: Sensory Models Of Memory Implicate An Epigenetic Mechanism O...mentioning
confidence: 99%
“…Subsequent studies have expanded on the role of epigenetic mechanisms in the IC – in particular, histone acetylation – to regulate aversive memory for conditioned taste. A 2014 study by Nuñez-Jaramillo and colleagues ( Núñez-Jaramillo et al, 2014 ) found that infusing the general class I HDAC inhibitor, sodium butyrate (NaB), in the IC during CTA strengthened the associative memory between the taste cue and malaise, which was revealed behaviorally as delayed extinction of the taste aversion. The same effect of HDAC inhibition on CTA memory was also reported by ( Rodríguez-Blanco et al, 2019 ) with post-training IC injections of the HDAC1/3-selective inhibitor MS-275 (“entinostat”).…”
Section: Sensory Models Of Memory Implicate An Epigenetic Mechanism O...mentioning
confidence: 99%